Metaâ€Analisis : Gender Dan Depresi Pada Remaja - Darmayanti, Nefi (Faculty of Psychology, Universitas Gadjah Mada, 2008)
The purpose of this metaâ€analysis study Â is Â to Â evaluate Â primary Â studies Â that Â studiedÂ gender Â differences Â in Â adolescents Â depression.Â Articles Â collected Â from Â popular Â journal Â (e.g.Â journal Â of Â research, Â journal Â of Â youthÂ adolescent, Â American Â journal Â of Â community Â psychology, Â journal Â of Â adolescence Â and Â psychology, Â journal Â of Â adolescence Â andÂ journal of abnormal child psychology). Twenty Â three Â articles Â were Â found, Â butÂ only Â fourteen Â articles Â were Â relevant. Â AfterÂ final Â evaluation, Â only Â twelve Â articles Â with Â fourteen studies could be analyzed. FourteenÂ (14) Â studies Â involving Â 5206 Â subjectsÂ examined Â gender Â differences Â in Â adolescents depression